2017
DOI: 10.1177/0160449x17744350
|View full text |Cite
|
Sign up to set email alerts
|

And Labor Came to Us: Making Use of an Opportune Workforce—Enhancing Migrant Integration into British Economy

Abstract: This article considers the opportunities presented by the availability of migrant labor in the U.K. employment market and its utilization. The research found that despite their qualifications, migrant labor is underutilized, thereby resulting in a readily available workforce being shunned and excluded from participative integration. This raises economic and ethical questions whose exploration revealed structural barriers (individually, communally, and institutionally) that impeded migrants' fulfillment of citi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…This research showed the relative importance of key socio-cultural barriers facing immigrant entrepreneurs in rural spheres such as Lincolnshire. Our findings are consistent with previous studies (Barnes and Cox, 2007; Hack-Polay and Mendy, 2017) who found that with the right support migrants can break out of the co-ethnic market and develop sustainable businesses in Lincolnshire. Additionally, this finding is exemplified in Fletcher’s (2017) study which found relatively high support for the argument that immigrants brought a different set of cultural experience to the Borough of Boston, a small town within Lincolnshire County, by moving into the area while opening shops and building lives.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This research showed the relative importance of key socio-cultural barriers facing immigrant entrepreneurs in rural spheres such as Lincolnshire. Our findings are consistent with previous studies (Barnes and Cox, 2007; Hack-Polay and Mendy, 2017) who found that with the right support migrants can break out of the co-ethnic market and develop sustainable businesses in Lincolnshire. Additionally, this finding is exemplified in Fletcher’s (2017) study which found relatively high support for the argument that immigrants brought a different set of cultural experience to the Borough of Boston, a small town within Lincolnshire County, by moving into the area while opening shops and building lives.…”
Section: Resultssupporting
confidence: 93%
“…a way out of unemployment and underemployment. Underemployment has been noted in contemporary research on the migrant workforce, and it refers to the insufficient use of worker skills or qualifications because the jobs available do not use the talents that the migrant workers harbour (Hack-Polay and Igwe, 2019; Hack-Polay and Mendy, 2017; Ikafa et al., 2020). Building on the functionalism philosophy in psychology, we define adaptation as the use of mental abilities to fit or cope with contextual/cultural changes.…”
Section: Introductionmentioning
confidence: 99%
“…Migrant mothers are often overlooked in public debates about citizenship and democracy. They mainly become visible in discourses of integration (Hack-Polay, 2016). Racialized groups of migrant mothers are portrayed as posing a risk to social and cultural cohesion, or standing in the way of their children’s successful integration into society, therefore threatening the very foundations of democracy (see Cameron, 2016).…”
Section: Migrant Mothers Enacting Citizenship – Deepening Processes Omentioning
confidence: 99%
“…Therefore, this study has noted insufficient e‐commerce and internet facilities in rural SMEs. As a result we propose that African firms' insufficient e‐commerce facilities have rendered network relationships internationally challenging (Hack‐Polay & Mendy, 2017). In the light of the earlier, we hypothesize that:H1c Lack of e‐commerce and internet is positively related to place barriers for rural SMEs' internationalization .…”
Section: Literature Reviewmentioning
confidence: 99%